Intersubjective violence and racist discrimination in schools: representations from teachers in Huanuco - Jacinto Pazos, Pedro (2017)
There are several words that are found in the vocabulary of the inhabitants of the region, and these are complemented when they explain the phrases that conjugate within these discriminatory expressions: “You are not good for nothing”. “You are a serrano”, “You are a shuco”, “Cholo smelly”, “Indio cochino”, “Cholo de m…”, “Cholo cochino”, “Serrano disgusting”. Teachers, when asked questions with agenda, many of the words and phrases described in a fun, which seemed to account for a fact that included them in their discriminatory form in which also They saw participants. In addition, the figures show that it is very common to hear racist words between students. Which agrees with all the nominations that have been made about it. And here, the first thing that comes out is the word “cholo”. But we must be careful, because we are with professors of the Sierra Huanuqueña where, the testimonial evidence call a person “cholo” as the sense of the Serrano or Andean.